Check and Balances dalam Sistem Peradilan Etik - Werdiningsih, Mega Ayu (Jurnal Konstitusi & Demokrasi, 2021)
The principle of checks and balances is closely related to the principle of separation of powers in the constitutional system, which in its development, the application of checks and balances emphasizes the importance of mutual control relationships between various branches of state administration, including within the scope of the judicial system. If in the legal justice system in the context of judicial power, the application of the principle of checks and balances is not new – that is through supervision by the House of Representatives (DPR) which is authorized to propose changes to the Supreme Court law and external supervision by the Judicial Commission (KY) on the behavior of judges according to the Code of Ethics-, therefore, the application of the principle of checks and balances should also be a concern in the ethical justice system. Considering, nowadays, the judicial system does not only include the legal justice system (Court of Law) but also includes the ethical justice system (Court of Ethics). For this reason, this paper examines the application of the principle of checks and balances in the ethical justice system, especially in the ethical justice system which still applies closed ethical trials, namely the Honorary Council of the DPR (MKD), the Honorary Council of Judges (MKH) and the Honorary Council of the Constitutional Court (MKMK). By knowing and paying attention to the application of the principle of checks and balances in the ethical justice system, it is hoped that the development of the ethical justice system (Court of Ethics) and the Court of Law will be implemented.